Integrated natural resource management in West African crop-livestock systems - Tarawali, Shirley A.; Keatinge, J.D.H.; Powell, J.M.; Hiernaux, Pierre H.Y.; Lyasse, O.; Sanginga, Nteranya (International Livestock Research Institute, 2004)
Integrated natural resource management (INRM) is considered in the context of evolving crop-livestock systems in West Africa and recent Developments in approaches for INRM research. The major crop-livestock systems, ranging from extensive grazing, through integrated crop-livestock farming to intensive peri-urban `industrial' type production are considered. Relationships between these systems and key INRM issues facing farmers in each are highlighted. Results of research aimed at improving and understanding crop-livestock production systems, followed by two examples of on-going INRM strategies from mixed farming systems in the region are discussed. Challenges and opportunities for research on INRM are discussed in relation to the evolving production systems. It is argued that by taking an INRM approach to research, institutions are beginning to address issues confronted and managed by farmers. With such an approach, interventions will be increasingly relevant and more readily adapted and widely adopted by smallholder farmers in the region. Key words: Balanced nutrient management systems, crop-livestock systems, integrated natural resource management, mixed farming.